Training on Application-Based Numeracy Literacy E-Assessment Development to Support AKM Readiness for Junior High School Teachers in Aceh Tamiang - Oktaviani, Coryna; Seprianto, Seprianto; Putri, Mentari Darma (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
The purpose of this service activity is to increase teachers’ knowledge, understanding, skills and creativity in preparing application-based Numeracy Literacy E-Assessments in supporting AKM readiness. The method of service activities is education and mentoring which consists of the preparation stage, implementation stage, and monitoring and evaluation stage. Pretest and posttest were conducted with 17 participants to determine the increase in participants' knowledge in the preparation of application-based Numeracy Literacy E-Assessment in supporting AKM readiness. Participant satisfaction with the service activities was measured using a questionnaire consisting of 12 indicators. The obtained data were analyzed using descriptive analysis. The results achieved from the implementation stage are the production of application-based numeracy literacy assessment products made by the participants themselves. The results of the evaluation stage by giving pretest and posttest showed that there was an increase in participants' knowledge in preparing application-based numeracy literacy assessments in the medium category with an n-gain value of 0.47. The results of the participant satisfaction questionnaire showed that 73.25% of the participants were satisfied while the other 26.75% were very satisfied with the service activities that had been carried out.